THE REALITY OF APPLYING MODERN FINANCIAL TECHNOLOGIES IN THE ISLAMIC BANKING INDUSTRY : THE EXPERIENCE OF SOUDI ARABIA - lazreg, fatima; nemer, Rabiha (Journal of Research in Finance and Accounting, 2023)
As modern financial technologies are one of the most interesting contemporary topics in the world and the Arab world, this study aimes to identify the reality of the application of financial technologies and their most important uses and achievements in the digitization of the Islamic banking industry in the Kingdom of Saudi Arabia and their repercussions on individual companies. The descriptive and analytical approach has been relied upon to describe various aspects of the subject and to clarify the contributions of financial technology in the development of new services and products developed in Islamic banking services within the framework of the Kingdom's goals 2030 and the fintech Saudi initiative. The study indicated that the digitization of Islamic banks of the Kingdom was a successful experience par excellence globally as the Kingdom is a key center for Islamic banking that led to the expansion of the network of customers and investors, it has become more demanding and faster to meet than before relying on digital applications as well as the establishment of digital banks according to transformational strategies, regulations and legislative regulations committed to the rules of Islamic Sharia.